Performance of f1 hybrids of arabica coffee with simultaneous resistance to leaf rust, bacterial blight and leaf miner - Andreazi, Elder; Sera, Gustavo Hiroshi; Faria, Ricardo Tadeu de; Sera, Tumoru; Shigueoka, Luciana Harumi; Carvalho, Filipe Gimenez; Carducci, Fernando César; Chamlet, Daniel (Coffee Science - ISSN 1984-3909, 2015)
The aim of this study was to select F1 hybrids with high yield, high vegetative vigor and simultaneous resistance to coffee leaf rust, bacterial blight and leaf miner. The experiments were set up in three different Paraná State municipalities: Londrina, at the experimental station of the Instituto Agronômico do Paraná (IAPAR); Congonhinhas and Itaguajé. Yield and plant growth traits were assessed, as well as resistance to coffee leaf rust, bacterial blight and leaf miner in 13 F1 hybrids and four commercial cultivars type pure lines used as control. Relative yield in relation to the mean value of the best line was estimated for all the hybrids. In all locations, hybrids 7, 11 and 12 had average yield significantly higher than the controls. Hybrids 6 and 9 were simultaneous resistant to leaf rust, bacterial blight and leaf miner. Hybrid 12 was resistant to leaf rust and bacterial blight. The hybrids 6, 7, 9, 11 and 12 have potential to become coffee cultivars.